Pengaruh Citra Perusahaan Dan Nilai Yang Dirasakan Terhadap Perilaku Konsumen Pada Primamedia Metro - Alif Rahman Thohir; Dharmawan; Jati Imantoro (Universitas Muhammadiyah Metro, 2025)
The development of business ventures in the current era of globalization is increasingly rapid, marked by an increasingly high and tight level of competition between companies. This situation causes companies in general to try to maintain survival, develop the company, obtain optimal profits and try to strengthen the company's position in facing competing companies. Primamedia Metro is a company that provides printing services to consumers from various circles. Based on the results of interviews conducted with owners regarding financial data, it shows that since the onset of COVID-19, it has resulted in losses, due to not being able to carry out normal business activities. The formulation of the problem in this research is 1) Is there an influence of company image on consumer behavior at Primamedia Metro? 2) Is there an influence of perceived value on consumer behavior at Primamedia Metro? 3) Is there an influence of company image and perceived value together on consumer behavior at Primamedia Metro? This research was carried out at Primamedia Metro using non-random sampling, namely purposive sampling of 90 respondents, namely Primamedia Metro consumers. The analysis technique in this research uses multiple linear regression tests with the SPSS application. From the research results it can be concluded that company image has a positive and significant influence on consumer behavior, perceived added value has a positive and significant influence on consumer behavior, and company image and perceived added value together have a positive and significant influence on consumer behavior.